Transition Metal Complex Catalyzed Photo- and Electrochemical (De)hydrogenations Involving C=O and C=N Bonds - Fokin, Igor; Kuessner, Kai-Thorben; Siewert, Inke (Synthesis, 2021)
Herein, we summarize the photo- and electrochemical protocols for dehydrogenation and hydrogenations involving carbonyl and imine functions. The three basic principles that have been explored to interconvert such moieties with transition metal complexes are discussed in detail and the substrate scope is evaluated. Furthermore, we describe some general thermodynamic and kinetic aspects of such electro- and photochemically driven reactions.1 Introduction2 Dehydrogenation Reactions2.1 Electrochemical Dehydrogenations Using High-Valent Metal Species2.2 Electrochemical Dehydrogenations Involving Metal Hydride species2.3 Photochemically Driven Dehydrogenation3 Hydrogenation Reactions3.1 Electrochemical Protocols3.2 Photochemical Protocols4 Conclusion5 Abbreviations
Keywords: dehydrogenations; hydrogenations; carbonyl compounds; homogeneous catalysis; photochemistry; electrochemistry; transition metal complexes